(untitled) (Research, Society and Development, 2021)
An approach to geography in a school discipline subject was presented in a challenging way for a large majority of their respective teachers, pois also seen the practice of a traditional pedagogical model, descriptive and memorable, outstanding in schools in the country. From this perspective, this revision work was carried out, having as a general objective to analyze or teach Geography in basic education. Its methodology was carried out by means of a literature review, with bibliographic surveys using books, articles and work on completion of the course, being a descriptive study with a qualitative approach. You have as a sample, Articles from main magazines such as Revista Rene, SciELO, lectures on the teaching of Federal Universities, scientific papers published in the Pedagogical Plan available at BNCC. Use of articles published in magazines, books of Ensino e dissertações da lngua Portuguese and English, published in 1998 at the days of the leaf. As a study procedure, initially a survey was made of two articles, books and lectures, selected from chave words such as Ensino e Geografia. As a conclusion, Geography is accompanied by the evolution of home, from the moment it emerged as a school discipline. As transformations or runs in the world inside, Geography seeks to accompany these trends, despite being very daring years traditional molds in such a discipline. Also, it is always necessary to be in debate and over-reflection on the part of those who are studying. This research sought to carry out a work of methodological analysis of the ensino of Geography in schools of basic ensino.